Juridical review of the implementation of social rehabilitation for TNI soldiers who abuse Class I Narcotics (Case study of Court Cassation Decision Agung Number 215 K/Mil/2019) - I Gede Sastrawan (Annals of Justice and Humanity, 2024)
Purpose: conduct research to find out the implementation of social rehabilitation in the military justice environment. Research methodology: In order to achieve scientific research, the methodology used is normative juridical using secondary data by researching the legal principles and elaborated with primary data, namely the results of interviews with the National Narcotics Agency of Sidoarjo Regency and the Military Correctional Institution III Surabaya. Results: The implementation of social rehabilitation in fact cannot be carried out according to the court decision, because the National Narcotics Agency of Sidoarjo Regency does not have social rehabilitation services and facilities, so medical rehabilitation in the form of consling is carried out as an alternative. The implementation of rehabilitation for the military has not been specifically regulated in the military judicial environment, so it is necessary to make regulations in the form of a TNI Commander Regulation that regulates the procedures, procedures, and mechanisms for the implementation of rehabilitation for the military.